Theophylline Revisited. Mechanisms, Challenges, and New Horizons - Jakub Szarłowicz; Michał Mazur; Dorota Waz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski; Sebastian Samuła (Quality in Sport)
Introduction and Purpose